Estimation of BER Bit Error Rate Using Digital Smoothing Filters - Jakub Peksinski (Kaunas University of Technology, 2021)
In the article, the authors present a new method of numerical determination of Q and BER parameters based on which the quality of transmission in optical fibre transmission systems is determined. The proposed method is based on the use of digital smoothing filters algorithms and does not require the knowledge of the so-called “eye diagram”, which greatly simplifies the entire measurement procedure. This method can be implemented in a simple manner in real-time systems, and in particular it is crucial for ICT systems and networks with a high bit rate of more than 10 Gbps and 40 Gbps and systems with time division or wavelength division multiplexing of 100 GBE and 400 GBE.